Analisis Hukum terhadap Perlindungan Whistleblower dalam Mendukung Kebebasan Berpendapat di Indonesia - Aina Pramita Sari; Akhmad Munawar; Lutfi Yusup Rahmathoni (Jurnal Hukum Lex Generalis, 2023)
Freedom of opinion and protection of whistleblowers are two critical aspects in maintaining transparency and accountability in Indonesia, particularly within the context of a healthy democracy. Article 28E, Paragraph (3), and Article 28F of the 1945 Constitution guarantee the right of every individual to express opinions, access information, and communicate freely. However, the implementation of freedom of opinion often faces obstacles, especially in relation to the ITE Law, which contains multi-interpretive articles, such as Article 27, Paragraph (3), and Article 28, Paragraph (2). These provisions are frequently used to criminalize individuals who express criticism or file public reports. This creates an imbalance between the right to freedom of expression guaranteed by the constitution and the inconsistent application of the law. This article also underscores the importance of legal protection for whistleblowers, who often face both physical and legal threats. While existing legal protections, such as Law No. 13 of 2006 in conjunction with Law No. 31 of 2014 regarding Witness and Victim Protection, provide a legal foundation, their implementation remains limited in the digital context. Therefore, harmonizing regulations, including revising the ITE Law, is essential to ensure that both freedom of expression and whistleblower protection are properly safeguarded. Reform in Indonesia's legal system is urgently needed to create a safe environment for the public to voice their opinions and report violations. This, in turn, will strengthen transparency, prevent corruption, and bolster democracy in Indonesia.